L’affaire Allstate et La Royale : la notion d’événement et les obligations des assureurs excédentaires, une solution propre au droit québécois - Jobin-Laberge, Odette (Assurances, 1995)
Mrs. Jobin-Laberge is a well-known author and legal practitioner. We are pleased to publish the speech she gave in Montréal on November 10, 1994, at a seminar organized by Les Éditions Yvon Blais Inc. Mrs. Jobin-Laberge comments on the recent Quebec Superior Court decision, by way of a Motion for a Declaratory Judgment, in the Allstate of Canada v. Royal lnsurance case. This is the first Quebec decision involving serial damages over a long period of time and the determination of the respective obligations of insurers, as primary and excess liability underwriters. While this issue has generared a considerable flow of American and European decisions, the "multiple trigger theory" had until now been untouched in Quebec. The Court studied the American decisions with caution and reserve in a Canadian context. The primary policy in force for the one-year period from December 31, 1979 to December 31, 1980 was found to be the sole primary policy engaging the responsibility of the insurer. Consequently, the applicable excess policy is the one issued for the period from April 30, 1980 to April 30, 1981.